Komunikasi Tokoh Pingkan dalam Merepresentasikan Konsep “Modern Meisje” Pada Novel Hujan Bulan Juni - Heri Isnaini (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The representation of female characters in the novel “Hujan Bulan Juni” by Sapardi Djoko Damono is based on the concept of "modern meisje" initiated by Kartini. This concept is an implication of the presentation of independent women who are in various ways able to become influential figures in society. The concept of "modern meisje" is represented through the character of Pingkan, the female character in the novel “Hujan Bulan Juni”. Pingkan is described as a mixed Manado-Javanese woman who has character as a "modern meisje" representation. This character can be seen in various signs seen in the portrayal of the character, both from physical depictions, characters, attitudes, and dialogue. This article aims to show the representation of Pingkan figures as "modern meisje" in accordance with Kartini's feminist concept. The method used in this study is a quantitataif descriptive method by placing the novel as research data. In addition, feminist studies become a theory that is used as a basis and reference in discussion. The results of the discussion showed that the figure of Pingkan is a figure who represents the concept of "modern meisje" in Kartini's view. This representation can be referenced in the concept of free women, independent, visionary, enthusiastic, and personal. This representation is conveyed by Kartini as part of the idealism of modern female figures in the view of feminism.